Principal component analysis and association between body composition and muscle strength variables in elite taekwondo athletes: An exploratory study - Cardozo, L. A.; Salcedo-Goméz, G. A.; Suárez, M. A.; Reina-Monroy, J.; Barón, Á. C.; Castillo-Daza, C. A.; Sáez de Villarreal Sáez, E. (Trends in Sport Sciences, 2025)
Introduction: Combat sports, especially taekwondo, require multi-component preparation programs; however, some are more determinant than others for sports performance.